URGENSI PEMBARUAN COMMERCIAL CODE DI BIDANG PELAYARAN GUNA MENJAMIN PERLINDUNGAN HUKUM KONSUMEN (STUDI PERBANDINGAN DI PELABUHAN PORTKLANG MALAYSIA) - Muhammad Syamsudin (Jurnal Media Hukum, 2014)
This study was aimed  to  reform some of  regulations of  the commercial code  in  shipping which are no  longer adequate  in  the  present development.  The main  issues  of  the  study  are:  (1)  How  is  the  development  of commercial  code  in  regulating  shipping matter  in  Indonesia?;  (2) Which  regulations of  the commercial  code are  necessarily  to  be  reviewed  to  guarantee  the  legal  protection  of  consumers?;  (3) How  is  the practice  of commercial code in Malaysia as a comparison in regulating the port in Indonesia?. The study uses the traditions of  normative  legal  research.  Legal materials  are  collected  by  studying  document  both  the  primary  legalmaterials and secondary  legal materials. Legal materials are analyzed by both of  themes  and content analysis. The analysis of  the  theme  is focused on  topics of commercial code  that needs  to be  reviewed. On the other hand,  the content analysis  is aimed  to  the contents of the  legal provisions of  the commercial code which are no longer appropriate , and it needs to be replaced by the new ones. The results of the study shows that there are some commercial code  regulations that need  to be reviewed namely: (1)  It relates to  the definition of the contract and  the parties  involved in  the making of  the contract;  (2)  It  is necessary to determine  the  limits of liability and responsibility of the carrier, and the protection of shippers (customers); (3) From the results of the comparative  studies  at  the  Port  Klang Malaysia demonstrate  that  normatively  Indonesia  is not  left behind  in terms of regulating commercial Code. It demonstrates that in practice Indonesia has imposed the Hage Visby Rules  1968,  although  Indonesia has  not  yet  ratified  it. On  the other hand, Malaysia  still  imposes  the Hague Rule 1924. The facts prove  that PortKlang  in Malaysia  is more advanced  than the ports  in  Indonesia  in terms of infrastructure availability. Portklang engagesin 13th rank among ports in the world, while the ports in Indonesia are not  included  in  the world rank.